(untitled) (Khairulummah, 2022)
Abstract Real prosperity and success is not implied in the modern economic system because it is according to the laws made by humans. In the modern era, since the economic system is capitalist, the poor are getting poorer and the rich are getting richer. The Prophet ﷺ laid the foundation of all the systems of Islam in his time in the light of the orders of the Lord of the worlds. While the Caliphs Rashiduns wrote down the best and easy Shari’ah for the Muslim Ummah by meticulously creating the consensus of the Ummah in these principles. The first caliph, Hazrat Abu Bakr Siddique, because he passed away in reforming the apostasy and deniers of zakat, while the second caliph, Hazrat Umar Farooq, who was the fruit of the prayers of the Holy Prophet, actually strengthened the religion from him. By laying the foundation stone of Police Department, Zakat and Agriculture Department and other systems, he presented organized systems based on strong laws. The fact is that in his time, justice was common not only to humans but also to animals. Farooq-e-Azam is such a role model and chapter of knowledge for us in the economic system that his economic thoughts and laws can build a best economic system and it is clear as day that he has created a best system in his time. Stabilized the Islamic economic system. The orders related to the factors of production and how to use these resources for the welfare of the Islamic state and Muslims are guidelines for the modern economic system. The application of the economic strategies of Hazrat Umar in the modern era. This title was chosen to highlight aspects.